Is extramedullary relapse of acute myeloid leukemia after allogeneic hematopoietic stem cell transplantation associated with improved survival?. Issue 3 (18th February 2013) - Curley, Cameron; Durrant, Simon; Kennedy, Glen A
Abstract Aims Recent reports have suggested that extramedullary (EM) relapse of acute myeloid leukemia (AML) post‐hematopoietic stem cell transplantation (HSCT), unlike isolated bone marrow (BM) relapse, is associated with improved prognosis. We reviewed the outcomes of relapsed AML post‐HSCT at our institution to determine whether survival for patients with EM relapse was truly improved in comparison to patients suffering BM relapses treated in a similar (active) way. Methods Outcomes of all 274 allogeneic HSCT performed for adult AML between 2000 and 2010 at our institution were retrospectively reviewed. Results As of January 2011, 72 relapses post‐HSCT had occurred, including 64 BM relapses (89%), two concomitant BM and EM relapses (3%), and six EM relapses alone (8%). EM relapses occurred significantly later post‐HSCT than BM relapses (median 25.2 vs 3.9 months, respectively; P = 0.001). Patients suffering an EM relapse were significantly more likely to receive active therapy at relapse (7/8; 88%) than those suffering a BM relapse alone (28/64; 44%; P = 0.026). When survival analysis was restricted to outcomes of patients treated actively (i.e., with curative intent), no difference in outcome between EM and BM relapses was observed (median survival 13.5 vs 8 months for EM vs BM relapses, respectively, P = 0.44). Conclusions Our results suggest that EM relapse post‐HSCT has similar outcomes to BM relapses treated in a similar way. Furthermore, choice of therapy at relapse appears related to the time post‐HSCT that the relapse occurs, with BM relapses occurring significantly earlier post‐HSCT than relapses at EM sites.